Konsep Diri Dengan Resiliensi Pada Sandwich Generation - Fatmasari, Dina; Ambarwati, Krismi Diah (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
Carrying out the roles of both a child and a parent at the same time is certainly not an easy thing to do. There are many responsibilities that must be carried out as individuals with the sandwich generation. The various problems faced certainly have an influence on the resilience of someone with the sandwich generation. To be a resilient individual certainly cannot be separated from the influence of a positive self-concept so that individuals in the sandwich generation are able to overcome every problem they experience. This research aims to determine the relationship between self-concept and resilience in individuals classified as the sandwich generation. The method used is quantitative with a correlational design. Participants in this research were 149 individuals from the sandwich generation. Research measurements used the Structure of the Personal Self-Concept (α = 0.879) and the Adiult Resilience Scale (α = 0.921). The analysis method uses the Sperm Rho correlation test. The research results show that there is a significant positive relationship between self-concept and resilience in individuals classified as the sandwich generation (r = 0.477) and sig. = 0.001. In this way, it is hoped that individuals who are classified as the sandwich generation can maintain a positive self-concept so that they remain resilient individuals in carrying out their role as a sandwich generation.